2016
DOI: 10.1590/1984-639820168543
|View full text |Cite
|
Sign up to set email alerts
|

Language learning apps or games: an investigation utilizing the RETAIN model

Abstract: ABSTRACT:Combining games with mobile devices can promote learning opportunities at the learners' fingertips and enable ubiquitous learning experiences. As teachers increasingly assign games to reinforce language learning, it becomes essential to evaluate how effective these applications are in helping students learn the content or develop the skills that the games are reinforcing. This article examines two English language learning apps under the RETAIN model (GUNTER; KENNY; VICK, 2008). The findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…Quadros (2014) considers the layout and the execution of the Duolingo lessons as a characteristic of gamification because of its ranking parameter for user performance displayed with progression bars and limited number of mistakes (3) indicated by3 hearts. However, in the present study Duolingo is considered a form of MALL and not of game because the analysis carried out by Gunter, Campbell, Braga, Racilan and Souza (2016) showed that Duolingo does not match the game category, despite presenting features of a game. Culbertson, Wang, Jung and Andersen (2016) suggest that Duolingo uses this game features to keep users engaged according to the RETAIN (Relevance, Embedding, Transfer, Adaptation, Immersion, Naturalization) evaluation model (Gunter;Kenny, & Vick, 2008 cited in Gunter;Campbell;Braga, Racilan, & Souza, 2016).…”
Section: Duolingomentioning
confidence: 80%
See 1 more Smart Citation
“…Quadros (2014) considers the layout and the execution of the Duolingo lessons as a characteristic of gamification because of its ranking parameter for user performance displayed with progression bars and limited number of mistakes (3) indicated by3 hearts. However, in the present study Duolingo is considered a form of MALL and not of game because the analysis carried out by Gunter, Campbell, Braga, Racilan and Souza (2016) showed that Duolingo does not match the game category, despite presenting features of a game. Culbertson, Wang, Jung and Andersen (2016) suggest that Duolingo uses this game features to keep users engaged according to the RETAIN (Relevance, Embedding, Transfer, Adaptation, Immersion, Naturalization) evaluation model (Gunter;Kenny, & Vick, 2008 cited in Gunter;Campbell;Braga, Racilan, & Souza, 2016).…”
Section: Duolingomentioning
confidence: 80%
“…However, in the present study Duolingo is considered a form of MALL and not of game because the analysis carried out by Gunter, Campbell, Braga, Racilan and Souza (2016) showed that Duolingo does not match the game category, despite presenting features of a game. Culbertson, Wang, Jung and Andersen (2016) suggest that Duolingo uses this game features to keep users engaged according to the RETAIN (Relevance, Embedding, Transfer, Adaptation, Immersion, Naturalization) evaluation model (Gunter;Kenny, & Vick, 2008 cited in Gunter;Campbell;Braga, Racilan, & Souza, 2016). These authors observed the weakest and strongest aspects of this app, though the evaluation was somewhat affected in some points because the model used for the evaluation is meant for analyzing games for educational purposes not and not apps.…”
Section: Duolingomentioning
confidence: 80%
“…Ahora bien, al revisar los resultados en función de las habilidades propias del aprendizaje de idiomas, aparece una relación estadísticamente significativa entre las habilidades de comprensión y expresión oral y comprensión escrita, indicando que los alumnos entienden que aprenden mejor con las Apps. El resultado es similar al hallado en las investigaciones realizadas por Alvarado et al (2016), Demouy et al (2016), García et al (2016), Gunter, et al (2016, Lindaman y Nolan (2015) y Martínez et. al (2016), que también consideraron que las Apps ayudan a trabajar de manera práctica los contenidos de la lengua e incrementan exponencialmente las oportunidades de aprendizaje.…”
Section: Discussionunclassified
“…Similar paired-associate translation tasks have been used to study word learning in general (e.g., Chow 2018; Kaushanskaya and Marian 2009), as well as the effects of word characteristics in particular (de Groot 2006; de Groot and Keijzer 2000; Kaushanskaya and Rechtzigel 2012). Although the relatively decontextualized nature of paired-associate learning may call the ecological validity of the task into question, repetition and memorization remain popular strategies among language learners (Ko and Goranson 2014), are still frequently used in language learning applications (Gunter et al 2016;Wu 2015) and, in some cases, have been shown to be as or more effective than tasks with higher levels of involvement load (e.g., Khoii and Sharififar 2013;Sagarra and Alba 2006). For example, rote memorization and paired-associate learning may be especially effective for more advanced learners (van Hell and Mahn 1997), as well as for establishing connections between form and meaning (Kasahara 2011).…”
Section: Introductionmentioning
confidence: 99%